Growth performance of nursery pigs fed biosaf in combination with in-feed antimicrobials - Hildabrand, B.M.; Burkey, T.E.; Skjolaas, K.A.; Johnson, B.J.; Minton, J. Ernest; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Weaned pigs (n = 240; initial BW 13.5 lb) were used in a 28-d growth study. Pigs were blocked by sex and BW, and were assigned randomly to 1 of the 5 dietary treatments: control (no added antimicrobials or yeasts), Neo- Terramycin4 (Neo-Terra; control diet plus Neo-Terra), Denagard5 (control diet plus Denagard PLUS), Neo-Terra+BIOSAF (control diet plus Neo-Terra and 0.15% BIOSAF yeast), or Denagard+BIOSAF (control diet plus Denagard and 0.15% BIOSAF yeast). There were 8 pens per treatment and 6 pigs per pen. Treatments were applied in both Phase 1 (d 0 to 14) and Phase 2 (d 15 to 28) diets. Overall (d 0 to 28), pigs fed Denagard+ BIOSAF had greater (P<0.05) ADG than all other treatments, and pigs fed Neo- Terra, Denagard, and Neo-Terra+BIOSAF had greater (P<0.05) ADG than did pigs fed the control diet. For the entire trial, pigs fed Denagard+ BIOSAF also had greater (P<0.05) ADFI than did pigs fed the control diet or diet containing Neo-Terra, but had ADFI similar to that of pigs fed Denagard and Neo- Terra+BIOSAF. Over the entire 28-d experiment, pigs fed Denagard+BIOSAF maintained greater (P<0.05) F/G than did pigs fed the control diet and diet containing Denagard. But F/G was similar between pigs fed Denagard+ BIOSAF, Neo-Terra+BIOSAF, and Neo-Terra. In summary, BIOSAF fed in combination with Denagard enhanced the growth response of nursery pigs beyond the growth advantage of Denagard alone. The interaction of BIOSAF with Denagard is generally consistent with other reports, although we anticipated that BIOSAF would also improve the response to Neo-Terra, as we had observed previously. Factors affecting the presence and magnitude of the interaction of BIOSAF and in-feed antibiotics to enhance the growth response in nursery pigs remain to be elucidated.
Keywords: Yeast; Antimicrobials; Denagard; Neo-Terra; Nursery pigs; Swine